Efficacy of the transvesical approach for robotic-assisted radical prostatectomy via a bladder neck and prostate combined longitudinal incision for the treatment of localized prostate cancer - Yang, YunKai; Wang, Jingyun; Zhang, DaHong; Zhang, Qi (Frontiers in Surgery, 2023)
Objective This study explores the feasibility and safety of the transvesical approach of robotic-assisted radical prostatectomy via a bladder neck and prostate combined longitudinal incision Methods From June 2017 to May 2021, 41 patients aged from 51 to 69 years underwent the transvesical approach of robotic-assisted radical prostatectomy via a bladder neck and prostate combined longitudinal incision (L-RALP). The prostate volume was 22.0～57.8 mL (mean: 36.3±11.1 mL), with a preoperative PSA value of 3.7 12.3 ng/ml (mean: 7.3 ± 1.2 ng/mL). All preoperative Gleason scores were less than or equal to 7 points, and the preoperative TNM stage ranged from T2a to T2b. All patients were diagnosed with prostate cancer by preoperative prostate biopsy or postoperative pathological specimens after prostatectomy. The operation, blood loss, hospitalization, and postoperative urinary continence were recorded. Results All the operations were completed by robotic-assisted radical prostatectomy without transition to open surgery. The surgery time was 105～131 min (mean: 111.3±14.9 min), with an estimated blood loss of 50 220 mL (mean: 95.5±27.3 mL). The postoperative hospital stay was 3 8 days (mean: 5.2±1.7 days), and the postoperative catheter was removed after 5 7 days (mean: 6.3±1.1 days). After 3 to 24 months of follow-up, 35 patients (85.4%, 35/41) recovered continence, 4 had no urine leakage after 1 week, and 2 had no urine leakage after 1 month. All patients had regained continence six months postoperatively. Conclusion The transvesical approach of robotic-assisted radical prostatectomy via a bladder neck and prostate combined longitudinal incision is a safe and effective surgical technique, beneficial for early continence recovery, and suitable for prostate cancer patients after prostate enucleation.